Prevalence and Patterns of Arrhythmias in ICU of a Tertiary Care Center in Nepal - Laudari, Shankar; Ghimire, Raksha; Subedi, Kumudini; Timilsena, Nabodit; Upadhyay, Hari Prasad (Journal of National Heart and Lung Society Nepal, 2024)
Background: Cardiac rhythm disorders, including atrial fibrillation (AF), supraventricular tachycardia (SVT), ventricular tachycardia (VT), and heart block, are common cardiovascular conditions associated with increased morbidity and mortality, particularly in elderly populations. Understanding the prevalence and clinical patterns of these disorders is essential for early diagnosis and effective management. The objective of this study is to determine the prevalence and patterns of cardiac rhythm disorders among patients attending a tertiary care center in Nepal. Methods: A descriptive observational study was conducted in ICU at Chitwan Mutu Hospital over a period of one year. A total of 110 patients with documented arrhythmias or conduction abnormalities on electrocardiogram (ECG) were included. Demographic data, type of arrhythmia, and presence of heart block were recorded using a pre-structured data collection sheet. Data were analyzed using SPSS version 17 and descriptive statistics such as frequencies and percentages were calculated. Results: The study population consisted predominantly of elderly patients, with 29.09% aged 71–80 years and 23.64% aged 61–70 years. The sex distribution was nearly equal (53.64% males, 55.45% females). AF with fast ventricular response (FVR) was the most common arrhythmia (50.91%), followed by paroxysmal supraventricular tachycardia (PSVT, 21.82%). VT and ventricular premature complexes (VPCs) were observed in 2.73% each. Among heart block disorders, third-degree or complete heart block (CHB) was present in 7.27% and second-degree block in 2.73%. Wolff–Parkinson–White (WPW) syndrome was noted in 5.45%, and sinus node dysfunction in 3.64%. Conclusion: Cardiac rhythm disorders, particularly AF with FVR, are more prevalent in older adults. Early detection and appropriate management are critical to reducing complications such as stroke, heart failure, and sudden cardiac death in this population.